Topology planning for autonomous MMGs: an ordered binary decision diagram‐based approach. Issue 1 (4th February 2020) - Khan, Hafiz Anwar Ullah; Al Hosani, Mohamed; Zeineldin, Hatem
Abstract : This paper finds its motivation from the perspective of utility planners, where the flexibility of choice while reconfiguring a distribution system into Multi‐Micrgrids (MMGs) is critical. To address the topology planning problem for MMGs from this dimension, a holistic algorithm incorporating graph theory, ordered binary decision diagrams, and a modified Gauss Siedel power flow algorithm is proposed. This multi‐indexed, multi‐tier scheme guarantees self‐adequacy and reliability of individual microgrids (MGs) by effectively solving a modified balanced partitioning problem, and ensures validation of inequality constraints through power flow studies. The available solutions are ranked according to two system‐level performance indices to provide a hierarchically feasible solution list to system planner. This algorithm is presented as an alternate tool for heuristic techniques to ensure a complete search of solution space and to increase the number of available topology planning solutions for the system operator. The flexibility of choice offered by this planning algorithm, tendency to be employed as a resource assessment tool, and incorporation of power flow analysis for autonomous MGs renders it to be practically superior to its counterparts. The proposed algorithm is tested to furnish its advantages and applicability in practical utility systems.